Implementasi Jaminan Produk Halal melalui Sertifikasi Halal pada Produk Makanan dan Minuman UMKM di Kabupaten Bandung - Febrianti, Ranti; Syahdiah, Ainun; Huwaida, Raden Luzna; Juliani, Dewi Sri (Fisip UIN Sunan Gunung Djati Bandung, 2024)
This paper is the result and discussion of research and community service KKN-Thematic Halal 2024 which discusses the implementation of Halal Product Guarantee through Halal Certification carried out in UMKM in Bandung Regency. The analytical tool used is using Merilee S. Grindle’s Policy Implementation theory. The discussion is carried out by analyzing and describing the indicators of Policy Implementation theory according to Merilee S. Grindle which consists of policy content and implementation context, where success is determined by the degree of implementability of the policy. The method used in this research uses a qualitative approach with a case study research design. The aim to be achieved is to describe how the implementation of a policy from Halal Product Guarantee on Halal Certificates for Food and Beverage UMKM in Bandung Regency. The findings of this study are that Bandung Regency has implemented policies related to Halal Product Guarantee in the form of Halal Certificates of the Free Halal Certificate Program (SEHATI). With the Halal Certificate Policy, UMKM Food and Beverage Business Actors in Bandung Regency benefit from the need for Halal Product Guarantee on their products by having Business Identification Number (NIB), Halal Certificate, and Halal Sticker.